An Approach Regarding the Use of Firewood as Fuel For Baking Pizzas in Masonry Ovens - Cezario, Luis Filipe Cabral (2024)
The use of firewood in masonry ovens for pizza preparation is a practice carried out in various regions of the world, in both domestic and commercial settings. It stands out as a source of renewable energy, low cost, and easy access. Most of the time, the firewood used for baking pizzas is not subjected to any quality selection process. The lack of quality discrimination of the firewood significantly contributes to the instability of the baking temperature of pizzas, the decrease in the energy efficiency of the combustion process, and mainly to the increase in emissions of atmospheric gaseous effluents. In this scenario, this study aimed to investigate the effects of firewood properties on the thermal profile of the oven and its implications on combustion and atmospheric emissions. Additionally, it aimed to analyze the influence of firewood as a fuel on the physical and chemical properties of pizza dough subjected to the baking process. For this purpose, Eucalyptus spp. firewood was divided into two batches by size: whole firewood and sectioned firewood. After size separation, each batch consisted of three moisture levels: oven-dried firewood (0% moisture), air-dried firewood (24% moisture, wet basis), and firewood composed of blends (initial oven ignition with 24% moisture firewood and subsequent feeding with anhydrous condition firewood). Thus, the study had six firewood variables, namely: i) W0 (oven-dried whole firewood); ii) W24 (air-dried whole firewood); iii) WB (whole firewood with blend); iv) S0 (oven-dried sectioned firewood); v) S24 (air-dried sectioned firewood); vi) SB (sectioned firewood with blend). The firewood was characterized physically (moisture and basic density), chemically (structural and elemental chemical composition), and energetically (higher, lower, and useful calorific value, TG/DTG, and energy density). For the pizza dough baking tests, the oven was subjected to a minimum temperature of 450 ºC, and the dough remained in baking for 150 seconds. Throughout all baking tests, the thermal performance of the oven and emissions of atmospheric pollutants (CO, CO2, NOx, and SO2) were investigated using thermocouples, a thermal imager, and a gas analyzer, respectively. Additionally, the physicochemical properties, proximate composition, and PAHs of the baked pizza doughs were analyzed. In general, the size and moisture content of the firewood influenced the ignition speed, temperature increase, and temperature residence time of the oven. Treatments W0 and S0 were responsible for the highest levels of atmospheric pollutant emissions, while treatments WB and SB were responsible for the lowest levels of emissions. The pizza doughs underwent changes in moisture, pH, and carbohydrate content. The amount of PAHs in the pizza doughs was not altered due to the use of firewood for baking. In summary, the baking process of pizzas in masonry ovens, when conducted properly and using firewood in blends, becomes more efficient and less polluting, without compromising the quality of the prepared pizzas.